Alkaline phosphatase activities in muscle of the euryhaline crab Chasmagnathus granulatus: Response to environmental salinity - Pinoni, Silvina Andrea (2005)
The occurrence, characteristics and response to environmental salinity of alkaline phosphatase (AP) activity were studied in chela muscle of the euryhaline crab Chasmagnathus granulatus from Mar Chiquita coastal lagoon (Buenos Aires Province, Argentina). Chela muscle exhibited a levamisole-insensitive and a levamisole-sensitive AP activities with distinct characteristics. Levamisole-insensitive activity appeared to be maximal at pH 7.7, whereas levamisole-sensitive AP activity was similar with the range of pH 7.4 to 8.0. Both activities at pH 7.7 exhibited a Michaelis-Menten kinetics (Km = 0.789 and 1.416 mM, respectively). I50 for levamisole-sensitive AP activity was about 12 mM. Levamisole-insensitive and levamisole-sensitive AP activities were differentially affected by temperature. Levamisole-sensitive AP activity was quite sensitive to temperature, exhibiting a peak at 37°C but being low at 5 to 30°C and 45 to 60°C. Both activities were inhibited by Cu2+. At 1.0 mM Cu2+, levamisole-insensitive AP activity was inhibited about 82% whereas levamisole-sensitive AP activity was almost completely inhibited. Levamisole-insensitive AP activity appeared to be sensitive to environmental salinity. In crabs acclimated to low salinity (10‰) this activity was lower than in 35‰ salinity. The response to environmental salinity suggests that levamisole-insensitive AP activity could be a component of muscle regulatory mechanisms at the biochemical level secondary to hyperregulation of C. granulatus. The possible physiological roles and functional relationship of AP activity with Na+/K+ ATPase in muscle are discussed.